Penerapan Sistem Presensi Jaringan Mobile Menggunakan Global Positioning System (GPS) dan Kamera pada Kantor Bank Mandiri Area Palembang Sudirman - Sarita Nabila (Institute of Information Technology and Social Science (IITSS), 2021)
The development of information technology and the internet is driving digital transformation in various company administrative activities, including employee attendance systems. Bank Mandiri's Palembang Sudirman Area Office still uses a fingerprint-based attendance system, which is considered less flexible, especially in conditions of heavy queues, power outages, and limited devices. This study aims to implement a mobile-based network attendance system using a camera and Global Positioning System (GPS) on Android devices to improve the effectiveness and flexibility of employee attendance. The research methods used include observation, interviews, and literature studies with a system design approach. The results show that the mobile-based attendance system allows employees to perform attendance independently via Android devices by validating selfie photos and location coordinates. Attendance data is automatically stored on the admin server and can be summarized quickly. Thus, the implementation of a mobile-based attendance system using a camera and GPS is proven to increase the efficiency of attendance management and make it easier for employees to perform daily attendance.